Antibacterial Activity of Cajuputi Oil (Melaleuca leucadendron) Microcapsules Against Staphylococcus aureus Bacteria Applied to Cotton Fabric Fibers - Sulistiyani, Indania Febry; Prasetya, Agung Tri (Universitas Negeri Semarang, 2022)
Essential oils were sensitive and easily degraded when exposed to oxygen, heat, and light. The microencapsulation technique is very suitable to protect the properties and activity of essential oils. The purpose of this study was to determine the effect of coating material composition on cajuputi leaf oil microcapsules. The microcapsules consist of core material and coating material. Cajuputi leaf oil was chosen as the core material for microcapsules because it has antibacterial activity with dominant components of 1,8-cineol of 55.43% and α-terpineol of 16.76%. Microcapsule coating materials used were maltodextrin and gum arabic with a ratio of 7:1; 6:2; 5:3; 4:4; 3:5; 2:6; and 1:7. From the results of the study, the microcapsules that had the best formulation were in the ratio of the coating material to 6:2 with a yield value of 82.35%; water content of 2.08%; particle size of 1.0512 m; and controlled release of 46%. Microcapsules with the best formulation tested by SEM produced irregular shapes, tested for the antibacterial activity of Staphylococcus aureus having an inhibition zone of 15 mm. The microcapsules with the best formulation were then immobilized into cotton fabric fibers with the help of polyurethane which was retested using SEM. The results of this cotton cloth will be used as a coating on cloth masks so that it has antibacterial properties.